Regulación de la senescencia foliar poscosecha por aplicación de ciclos de luz oscuridad en berro (Nasturtium officinale R. Br.) - Carreón Hidalgo, Juan Pablo (Universidad Autónoma Metropolitana, 2017)
In the present study, the effect of 12 h/12 h light/dark cycles on the postharvest quality of the watercress (Nasturtium officinale R. Br.) during storage at 4 and 10 °C was evaluated for a total of seven days. Specifically, values for parameters such as total chlorophyll, total carotenoids and total soluble protein, as well as those for postharvest variables such as color (measured in terms of a*, b*, L* and h* co-ordinates) and percentage weight loss, were determined both in individual leaves and stems tied in bundles. The study was carried out sequentially in four different experiments with the main objective being that of determining the effect of light-dark cycles on different presentations of watercress (leaves and bundles) and refrigerated storage conditions (4 and 10 °C). In experiments three and four, the results obtained with watercress were compared to those obtained with the model plant Arabidopsis thaliana. At a refrigerated storage temperature of 10 °C, significant differences were obtained between light-dark treatments and controls (continuous darkness) for most of the variables studied in both leaves and bundles. For example, in all light-dark treatments a decrease in the content of chlorophyll, carotenoids and soluble protein could be delayed over the course of one or more days of storage, as could be the progression toward more yellowish tonalities (changes in a*, b*, L* and h* co-ordinates) from the original green coloration of samples. However, higher values were obtained for the same treatments in terms of percentage weight loss, although the recommended limit of 7% for watercress was never exceeded in all cases. On the other hand, only some differences were observed between A. thaliana stored at 10 °C and the leaves and bundles of watercress stored at 4 °C. Specifically, a decrease in the content of chlorophyll and carotenoids in both organisms could be delayed after treatment with lightdark cycles. Percentage weight loss was also similar to that observed in previous experiments, with higher values obtained in light-dark treatments. These results suggest that at low refrigerated storage temperatures (i.e. 4 °C) the effect of light-dark cycles ceases to be relevant because of a decrease in the metabolic activity of the plant material.; En el presente estudio se evaluó el efecto de la aplicación de ciclos 12 h/ 12 h luz oscuridad durante el almacenamiento poscosecha a 4 y 10 °C por siete días en hojas y manojos de berro (Nasturtium officinale R. Br.) sobre los niveles de clorofila total, carotenoides totales y proteína soluble, así como en variables poscosecha como el color (parámetros cromáticos a*, b*, L* y h*) y el porcentaje de pérdida de peso. El estudio se llevó a cabo de forma secuencial en cuatro experimentos con el objetivo principal de determinar el efecto de la aplicación de los ciclos luz oscuridad en diferentes presentaciones de berro (hoja y manojos) y condiciones de almacenamiento refrigerado (4 y 10 °C). En el experimento tres y cuatro los resultados obtenidos en berro fueron comparados con la planta modelo Arabidopsis thaliana. A una temperatura de almacenamiento refrigerado de 10 °C se obtuvieron diferencias significativas entre el tratamiento de luz oscuridad y un control (oscuridad continua) para la mayor parte de las variables estudiadas tanto en hojas como en manojos de berro. En clorofila, carotenoides y proteína soluble se observó un retraso en la disminución del contenido de estos componentes en uno o más días de almacenamiento para el tratamiento de luz oscuridad. En los parámetros a*, b*, L* y h* se observó un paso más lento de tonalidades verdes a amarillas por el efecto de la aplicación de ciclos luz oscuridad, mientras que en el caso del porcentaje de pérdida de peso se registraron valores mayores para este mismo tratamiento, pero sin sobrepasar en el caso de manojos, el límite recomendado de pérdida de peso para berro (7%). En A. thaliana almacenada a 10 °C y en hojas y manojos de berro almacenados a 4 °C se observaron diferencias en sólo en algunas variables, como en el caso de clorofila total y carotenoides totales, observándose una tendencia al retraso en la disminución del contenido de estos componentes por la aplicación de los ciclos luz oscuridad. La pérdida de peso mostró comportamientos similares en estos experimentos, con pérdidas mayores para el tratamiento de luz oscuridad. Estos resultados podrían indicar que a bajas temperaturas de almacenamiento refrigerado (4 °C) el efecto de los ciclos luz oscuridad deja de ser tan relevante debido a la reducción de la actividad metabólica.